PELATIHAN KUMANDANG ADZAN DAN IQAMAH PADA SANTRI TAMAN PENDIDIKAN AL-QUR’AN MASJID AL-MU’MIN - Prima, Anggra; Syafi’i, Muhammad Imam; Sunayah, Sunayah; Israil, Muh. (El-Madaniyah : Jurnal Pengabdian Masyarakat, 2024)
Training in singing the Azan and Iqamah among TPA students is very important, but often this training has not received serious attention, so the skills in singing the Azan and Iqamah among TPA students are not optimal. The aim of this service is to explore training in giving the call to prayer and Iqamah for TPA students. The method for implementing this service uses participatory action research (PAR). The results of the service are that the implementation of activities begins by conducting a survey at the Al-Mu'min Mosque TPA; the second stage is providing information to the TPA teachers to hold Adhan and Iqamah training; and the third stage is carrying out training activities. The results of the activity show that the children of the Al-Mu'min Mosque TPA in Lake Redan Village have the ability to pronounce the Adhan and Iqamah well, so it can be concluded that the Adhan and Iqamah training program will run smoothly and in line with expectations. It is hoped that this service can contribute to improving the quality of Islamic religious education in the TPA environment, as well as help strengthen the religious identity and Islamic skills of students as a competent next generation